Pengaruh Metode Outdoor Learning terhadap Hasil Belajar Kognitif Siswa pada Mata Pelajaran IPAS Kelas VI SDN 2 Kembangbahu - Habib Maulana Achsan; Ade Cyntia Pritasari (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
This research aims to determine whether or not there is an influence of the use of outdoor learning methods on students' cognitive learning outcomes in class VI science and science subjects at SDN 2 Kembangbahu. This research is a quantitative research type of experimental research, using a One-Group Pre-test-Post-test Design. The sample used was 16 students. Data collected used pre-test and post-test questions. The results of the research show that there is an influence in the use of outdoor learning methods on students' cognitive learning outcomes. The magnitude of the influence is proven from the results of the paired sample t-test. The calculation results obtained a significance value of 0.000. Based on the test criteria if the Sig. (2-tailed) < 0.05 then H0 is rejected and Ha is accepted, and if the t-count value > t-table (9.638 > 2,131) then H0 is rejected and Ha is accepted. So it can be concluded that there is an influence on the application of the Outdoor Learning method on students' cognitive learning outcomes in class VI science and science subjects at SDN 2 Kembangbahu.